The olfactory sense and its manifestation in Philippine languages - Balisi, Rolien Mark M. (2021)
Access online through this link: https://journals.upd.edu.ph/index.php/Dunong/article/view/8816/7774
Keywords: Philippine languages; Linguistics; Smell